Case Report: PD-1 Inhibitor Is Active in Lung Adenocarcinoma With B Cell Deficiency - Yuan, Shumin; Hu, Xiufeng; Zhao, Yanqiu; Wang, Zibing (Frontiers in Immunology, 2020)
Introduction In murine cancer models, B cells are unnecessary for efficacy of PD-1 inhibitor. However, we do not know whether this applies to clinical settings, especially in patients with non-small-cell lung carcinoma (NSCLC). Case presentation We report on the case of an advanced lung adenocarcinoma patient without oncogenic driver mutations whose disease progressed on second-line bevacizumab-containing chemotherapy regimens. These previous treatments resulted in profound thrombocytopenia and increased number of B cells; both effects were hard to alleviate. The patient was diagnosed with marginal zone B-cell lymphoma by flow cytometry immunophenotyping. After five cycles of rituximab in combination with lenalidomide treatment, the percentage of B cells rapidly declined to undetectable levels and the lymphoma regressed completely. However, because masses in the lung gradually increased, this patient was subsequently treated with a PD-1 inhibitor. The patient’s condition stabilized, and the mass shrank to reach partial response, with progression free survival exceeding 15 months and no serious adverse events. Conclusion The present case proves the efficacy of PD-1 inhibitor in metastatic lung adenocarcinoma in the absence of B cells. Immune checkpoint inhibitions are thus a choice for patients with B cell deficiencies, such as X-linked agammaglobulinemia, immunoglobulin deficiencies, and common variable immunodeficiency, diseases that have historically been excluded from clinical trials for oncologic drugs.